2023
DOI: 10.3390/ijms242316984
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Potential Biomarkers of Environmental Exposure to Polycyclic Aromatic Hydrocarbons and Their Link with Inflammation and Lung Cancer

Pablo Letelier,
Rolando Saldías,
Pía Loren
et al.

Abstract: Exposure to atmospheric air pollution containing volatile organic compounds such as polycyclic aromatic hydrocarbons (PAHs) has been shown to be a risk factor in the induction of lung inflammation and the initiation and progression of lung cancer. MicroRNAs (miRNAs) are small single-stranded non-coding RNA molecules of ~20–22 nucleotides that regulate different physiological processes, and their altered expression is implicated in various pathophysiological conditions. Recent studies have shown that the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 219 publications
0
4
0
Order By: Relevance
“…All primary mutation types, involving single nucleotide variations, deletions, rearrangements, insertions, and copy number alterations can be found using cancer-personalized profiling by deep sequencing (CAPP-Seq). It’s crucial to bear in mind that CAPP-Seq has limitations regarding the types of mutations it can discover ( 16 , 25 ). Whole genome sequencing (WGS) is a comprehensive approach that examines a tumor’s complete genomic content, which can greatly aid therapeutic decision-making and reveal novel therapy plans, unusual mutations, and invisible oncogenes.…”
Section: Technologies For Ctcs、ctdna and Ev Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…All primary mutation types, involving single nucleotide variations, deletions, rearrangements, insertions, and copy number alterations can be found using cancer-personalized profiling by deep sequencing (CAPP-Seq). It’s crucial to bear in mind that CAPP-Seq has limitations regarding the types of mutations it can discover ( 16 , 25 ). Whole genome sequencing (WGS) is a comprehensive approach that examines a tumor’s complete genomic content, which can greatly aid therapeutic decision-making and reveal novel therapy plans, unusual mutations, and invisible oncogenes.…”
Section: Technologies For Ctcs、ctdna and Ev Detectionmentioning
confidence: 99%
“…EVs contain cargoes of miRNAs,mRNAs, and proteins. It has been shown that microRNAs carried by EVs are associated with colorectal cancer ( 14 ), hepatocellular carcinoma ( 15 ), lung cancer ( 16 ), oral cancer ( 17 ), and ovarian cancer ( 18 ). The contents of EVs such as mRNA can promote epithelial-mesenchymal transition and chemoresistance in colorectal cancer ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of short-term effects, studies within school populations have identified a decline in lung function, heightened instances of airway inflammation, and an escalated likelihood of developing lung cancer among those consistently exposed to HC over an extended period [10,17]. Nitrogen oxides (NOx)…”
Section: Hydrocarbons (Hc)mentioning
confidence: 99%
“…Currently, the miRBase database ( ; accessed in 1 December 2023) lists over 2588 distinct miRNAs that are involved in nearly every cellular process, highlighting the vast and complex nature of this field of study [ 7 , 8 ]. Moreover, alterations in miRNA expression have been implicated in a myriad of diseases, emphasizing their importance in maintaining cellular homeostasis [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%